The effects of water and non‐nutritive sweetened beverages on weight loss and weight maintenance: A randomized clinical trial. (26th December 2015) - Peters, John C.; Beck, Jimikaye; Cardel, Michelle; Wyatt, Holly R.; Foster, Gary D.; Pan, Zhaoxing; Wojtanowski, Alexis C.; Vander Veur, Stephanie S.; Herring, Sharon J.; Brill, Carrie; Hill, James O.
Abstract : Objective: To evaluate the effects of water versus beverages sweetened with non‐nutritive sweeteners (NNS) on body weight in subjects enrolled in a year‐long behavioral weight loss treatment program. Methods: The study used a randomized equivalence design with NNS or water beverages as the main factor in a trial among 303 weight‐stable people with overweight and obesity. All participants participated in a weight loss program plus assignment to consume 24 ounces (710 ml) of water or NNS beverages daily for 1 year. Results: NNS and water treatments were non‐equivalent, with NNS treatment showing greater weight loss at the end of 1 year. At 1 year subjects receiving water had maintained a 2.45 ± 5.59 kg weight loss while those receiving NNS beverages maintained a loss of 6.21 ± 7.65 kg ( P < 0.001 for difference). Conclusions: Water and NNS beverages were not equivalent for weight loss and maintenance during a 1‐year behavioral treatment program. NNS beverages were superior for weight loss and weight maintenance in a population consisting of regular users of NNS beverages who either maintained or discontinued consumption of these beverages and consumed water during a structured weight loss program. These results suggest that NNS beverages can be an effective tool for weight loss and maintenance within the context of a weight management program.